2011
DOI: 10.9734/ijbcrr/2011/164
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Juice Is Potentially Better Than Orange Juice in Improving Antioxidant Function in Elderly Subjects

Abstract: In the present study, 26 elderly subjects were recruited and randomly divided into 2 groups, that is, orange (low in antioxidant capacity) and pomegranate (high in antioxidant capacity) groups, and 250 mL of juice was consumed daily for 4 weeks. Changes in plasma antioxidant capacity, activity of antioxidant enzymes, contents of ascorbic acid, vitamin E, reduced glutathione, malondialdehyde, oxidized low-density lipoprotein and carbonyls, and the degree of DNA damage in mononuclear blood cells were measured. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Pomegranate, an ET‐rich fruit crop, is a widely used source of dietary polyphenols. An analysis of the antioxidant activity of various dietary supplements has shown that the antioxidant activity of pomegranate juice exceeds that of orange juice (Parashar, ), milk thistle, green tea, grape seed, goji, acai (Henning et al ., ) and infusions of red wine or green tea (Gil et al ., ). In addition to antioxidant function, EA and punicalagins in pomegranate have been implicated as potent anticancer and antiatherosclerotic agents (Adams et al ., ; Viuda‐Martos et al ., ; Usta et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate, an ET‐rich fruit crop, is a widely used source of dietary polyphenols. An analysis of the antioxidant activity of various dietary supplements has shown that the antioxidant activity of pomegranate juice exceeds that of orange juice (Parashar, ), milk thistle, green tea, grape seed, goji, acai (Henning et al ., ) and infusions of red wine or green tea (Gil et al ., ). In addition to antioxidant function, EA and punicalagins in pomegranate have been implicated as potent anticancer and antiatherosclerotic agents (Adams et al ., ; Viuda‐Martos et al ., ; Usta et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…EA, on the other hand, restored cognitive performance related to mild age-related declines in overweight participants aged around 50 years after 12 weeks EA treatment course [16]. Supplementation with EA-rich foods and beverages as pomegranate juice has been shown to improve the antioxidant status in aged healthy humans (aged over 60 years) after four weeks of treatment [17,18]. LA and EA derivatives and some supplements representing a rich source of both have been tested on humans, and have improved some symptoms that also occur in PD.…”
Section: Introductionmentioning
confidence: 99%
“…The 28 studies ( n = 1089) included evaluated the effects of consumption of fruit or vegetable juices on healthy people or patients who had chronic diseases or a debilitating condition (e.g., diabetes, cancer, hemodialysis) [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]. Most studies (75%) utilized a parallel design and 17 of them used a placebo juice (mainly composed by flavored water and sucralose) for comparison.…”
Section: Resultsmentioning
confidence: 99%